Oilerio sandaugų analizinio pratęsimo klausimu - Stankus, Eugenijus (Lietuvos matematikos rinkinys, 2000)
The sequence of generalized primes v(p + kpα) with rational prime numbers p and v > 1/2, 0≤ k ≤ 1, 0 ≤ α < 1 is considered. The analicity of corresponding Euler product Z (s; v, k, α)= ∏p (1 — (v (p + kpα))-s)-1 in the domain s : σ > α (∪ρ∪n s= (xβ+ iγ)/n : α < x ≤ 1 ∪ (α; 1]), where ρ = β + iγ are the zeros of Riemann zeta function, is proved.